Analisis Kinerja Keuangan Pada Dinas Pendidikan Daerah Provinsi Sulawesi Utara - Bantali, Yosua; Gamaliel, Hendrik; Walandow, Stanley Kho (Universitas Sam Ratulangi, 2024)
The research is to determine whether the financial performance of the Regional EducationOffice of North Sulawesi Province in 2023 has met the Value for Money requirements. Fromthree elements, namely Economics, Efficiency and Effectiveness. This type of research uses aqualitative descriptive method. The data collection techniques used were interviews anddocumentation. The financial performance results obtained by the Regional Education Officeof North Sulawesi Province met the economic requirements, namely 87,48% of 3 mainactivity programs, for the efficiency ratio the results were 151% inefficient and for theeffectiveness ratio the results were effectiveness, namely 100%